653 Benzene and work on deck on product tankers: exposures, benzene in exhaled air and urinary biomarkers of benzene exposure. (24th April 2018) - Forsell, K; Ljungkvist, G; Nordlinder, R; Andersson, E; Nilsson, R
Abstract : Introduction: Increased rates of leukaemia have been found among tanker crews. The leukemic carcinogen benzene is a plausible cause, but serving on tankers is not an established risk occupation for leukaemia. Studies on tankers have revealed exposure to benzene, although with inconsistent exposure levels and without toxicological data. We present exposure to benzene together with biomarkers for benzene uptake, metabolism and genotoxic effects on Swedish product chemical tankers. Methods: Between 1995 and 1998, 37 seafarers (20 deck crew members, 17 not on deck) on seven different product chemical tankers, wore personal passive breathing zone dosimeters. Each individual was monitored with timed samples for benzene in end-exhaled (alveolar) air and in urine for unmetabolized benzene, the benzene metabolite tt-muconic acid (t, t-MA) and 8-hydroxydeoxyguanosine (8-OHdG), a marker of DNA oxidative stress. Samples were taken before and following a watch for up to 24 hours. Result: The average concentration of benzene in air during a watch (approximately 4 hour) displayed a wide range depending on work task performed (range 0 to 50 mg/m3; peak 143 mg/m3). All biomarkers were low/undetectable before and elevated after benzene exposure tasks. Peaks for t, t-MA and 8OHdG occurred after 5 and 13 hours, resp. The time needed for returning to pre-'work task' values were in ascending order alveolar benzene, U-benzene, U-t, t-MA and U-8OdG. Controls had low levels of urinary biomarkers and without diurnal variations. Discussion: Several work tasks resulted in high exposure to benzene, often exceeding the Swedish occupational exposure limit (1.5 mg/m3, 8hTWA). Benzene exposure resulted in oxidative damage to DNA in cells, indicating that work on tankers might induce genotoxic effects in the human body. The finding suggest a plausible mechanism between cause and effect in coherence with epidemiological findings for increased risk of leukaemia in tanker crews.